Design of Space-Based Carbon Dioxide Measuring Sensor Device - Maulana, Wildan; Zulfikar, Zulfikar (NEWTON: Networking and Information Technology, 2024)
This study aims to design and build a sensor device that can measure carbon dioxide (CO2) gas levels in Islamic boarding schools and universities using the MQ-135 sensor and Arduino microcontroller. The research methods used include designing hardware and software that can detect and display CO2 levels in real-time. This tool is designed by utilizing the MQ-135 sensor connected to the Arduino microcontroller, equipped with an LCD screen to display the measurement results. Testing was carried out to ensure the accuracy and reliability of the tool in measuring CO2 levels. In addition, this tool is also designed to provide notification if CO2 levels exceed the specified safe limit. The results of the study showed that the designed tool successfully detected CO2 levels well and provided accurate readings. The notifications provided by the tool also functioned effectively, providing early warning to residents when CO2 levels increased. The results of the tool test showed that this sensor tool can be an effective solution for monitoring indoor air quality and helping to maintain the health of residents. Further implementation and testing in various environmental conditions are recommended to improve the performance and reliability of this tool. Thus, this sensor device can provide greater benefits in maintaining air quality and health in the household environment.